1971
DOI: 10.1002/eji.1830010312
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the inferferon‐like virus inhibitor released during interaction of mouse sensitized lymphocytes with their target cells

Abstract: The properties of an interferon-like viral inhibitor (ILVI) released during the interaction of sensitized mouse peritoneal and/or splenic leukocytes with L-cells were studied.In addition to such properties as trypsin sensitivity, thermoresistance at 56 O C , resistance to acid pH, species specificity, cell mediated effect, etc., it has been shown that actinomycin D, puromycin and cycloheximide prevent the antiviral action of ILVI to the same extent as in the case of other interferons. The molecular weight of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…I t is important for investigators studying the inhibitory effects of either of these two molecules in supernatants from stimulated leucocytes to realize that both molecules are often present (2).…”
Section: Discussionmentioning
confidence: 99%
“…I t is important for investigators studying the inhibitory effects of either of these two molecules in supernatants from stimulated leucocytes to realize that both molecules are often present (2).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon has been found to be one of the mediators of cell-mediated immunity (7,10,20). It is produced in vitro upon exposure of human or mouse leukocytes to mitogens and to viral or nonviral antigens (4,6,9,18…”
Section: Y Ito Et Almentioning
confidence: 99%
“…In 1966, Glasgow provided the first direct evidence of the fact that immunity and immune mechanisms are intimately associated with interferon production (10). Subsequent experiments demonstrated that nonviral antigens stimulated interferon production in cultures of lymphocytes from sensitized donors but not in cultures from donors who lack sensitivity to those antigens (4,6,9). These results suggest that the induction of interferon may be an essential part of the immune response.…”
mentioning
confidence: 99%